2012
DOI: 10.1097/fpc.0b013e32835516e5
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the transcription factor NRF2 and forearm vasodilator responses in humans

Abstract: Objective Oxidative stress is integral to the development of endothelial dysfunction and cardiovascular disease. As NRF2 is a key transcription factor in antioxidant defense, we aimed to determine whether polymorphisms within the promoter region of the gene encoding NRF2 (NFE2L2) would significantly modify vasodilator responses in humans. Methods Associations between the – 653A/G (rs35652124), – 651G/A (rs6706649), and – 617C/A (rs6721961) polymorphisms within the NFE2L2 promoter and vascular function were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 27 publications
0
43
1
1
Order By: Relevance
“…Gene set We also investigated how NRF2 coordinates the regulation of these key metabolic pathways. Global mapping of NRF2 binding sites in Keap1 -/-MEFs and human lymphoblastoid cell lines identified a strong NRF2 binding site at the TALDO1 locus (<1 kb from the TSS), within an intron (2,49). However, NRF2 binding to the G6PD and PGD loci was not validated in the human lymphoblastoid cell line (49).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene set We also investigated how NRF2 coordinates the regulation of these key metabolic pathways. Global mapping of NRF2 binding sites in Keap1 -/-MEFs and human lymphoblastoid cell lines identified a strong NRF2 binding site at the TALDO1 locus (<1 kb from the TSS), within an intron (2,49). However, NRF2 binding to the G6PD and PGD loci was not validated in the human lymphoblastoid cell line (49).…”
Section: Methodsmentioning
confidence: 99%
“…However, NRF2 binding to the G6PD and PGD loci was not validated in the human lymphoblastoid cell line (49). Last, the NRF2 binding site in the human and murine TKT loci was located at greater than 14 kb upstream of the TSS, suggesting that PPP genes (G6PD, TKT, and PGD) are not direct transcriptional targets of NRF2 (2,49). Remarkably, we found that PPP activity is regulated by miRNAs miR-1 and miR-206, and that NRF2 upregulates the expression of PPP enzymes by attenuating the expression of these 2 miRNA species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other hand, in White Americans, −617A variant allele carriers had significantly higher FVR. Polymorphisms within the NFE2L2 promoter were associated with impaired forearm vasodilator responses in an endothelial-independent manner, suggesting an important role of NRF2 in the regulation of vascular function in humans [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some of the SNPs are supposed to affect NRF2 transcriptional activity and may impact both transcription and translation of downstream detoxifying and antioxidant genes. Previous studies showed that NRF2 SNPs were correlated with lower lung function (Masuko et al, 2011), development of inflammatory disease (Siedlinski et al, 2009), and impaired regulation of vascular function (Marczak et al, 2012). Genetic polymorphism of NRF2 on several SNPs (including rs6721961 and rs2886162) were associated with breast cancer risk (Hartikainen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%